Regulatory effects of traditional Chinese medicine on the breast-cancer immune microenvironment - Liu, Ting; Shang, Jingying; Wang, Jiameng; Han, Lutuo; Yang, Mingyue; Li, Ruonan; Ni, Baoyi; Jiang, Jiakang (Frontiers in Immunology, 2026)
Breast cancer (BC) is the most common malignant tumor in women, driven by various factors. Its incidence has been rising annually and has become an urgent global public health challenge. An increasing body of evidence suggests that the immune microenvironment (IME) of breast cancer plays a crucial role in tumor initiation, progression, and metastasis. Through multi-target and multi-pathway regulatory effects, Traditional Chinese Medicine (TCM) demonstrates unique potential in reshaping the tumor immune microenvironment (TIME). This narrative review aims to systematically organize and summarize recent mechanistic advancements, elucidating how Traditional Chinese Medicine (primarily based on Chinese herbal medicine) regulates the function and polarization of key immune cells, controls immune checkpoints and cytokine networks, thereby inhibiting tumor immune escape, enhancing anti-tumor immunity, and exerting anti-BC effects. Despite the promising prospects, the application of TCM in BC immunotherapy still faces numerous challenges, including tumor heterogeneity, dosage complexity, and safety issues. Future research should focus on large-scale, multi-center clinical trials combining contemporary immunotherapy strategies, aiming to achieve better clinical outcomes in BC treatment and provide insights for immunotherapy of other cancer types.